Answer:
(6,-2.5)
Step-by-step explanation:
The formula for the midpoint between two points is:
Now we substitute
We have than (9, -1) is and (3, - 4) is
So:
So, we have:
<h2>(6,-2.5)</h2><h2 />
I can do a graphic explanation if you want.
For every , we have
So, negletting the first term, each term of the sum is greater than 1, which implies
Which means that the series diverges.
The solution (-4,2) satisfies for the system of linear equations 3x + 13y = 14; 6x + 11y = -2
<u>Step-by-step explanation:</u>
Step 1:
Given detail is the solution of the equations (-4, 2) ie, x= - 4 and y = 2
This implies that this solution should satisfy the given linear equations.
Step 2:
Substitute values of x and y in the equations and verify whether the right hand side equals the left hand side.
System 1 Eq(1) ⇒ LHS = 3(-4) + 13 (2) = -12 + 26 = 14 = RHS
System 1 Eq(2) ⇒ LHS = 6(-4) + 11(2) = -24 + 22 = -2 = RHS
Therefore, the first system of linear equations satisfy the condition.
Complete the equivalent equation for –7x<span> – 60 = </span>x2<span> + 10</span>x.
(x<span> + 5</span>)(x<span> + 12) = 0</span>
What are the solutions of –7x<span> – 60 = </span>x2<span> + 10</span>x?
x<span> = -12 or -5</span>
Please mark as Brainliest.